0721 Coronary Atherosclerotic Plaque Burden and Composition in Patients with Obstructive Sleep Apnea by Coronary CT Angiography. (27th May 2020) - Lu, M; Wei, Y; Wang, Z; Fang, F; John, S E; Xu, L
Abstract: Introduction: OSA is closely associated with increased risk of coronary artery disease. Although previous small studies have investigated coronary plaque in OSA patients, limited data are available regarding the association of OSA with plaque morphology and composition. Therefore, we aimed to quantitatively characterize and compare coronary plaque burden and composition between patients with no or mild obstructive sleep apnea (OSA) and moderate-severe OSA using coronary computed tomography angiography (CTA) in a large-scale study. Methods: We retrospectively analyzed consecutive patients who underwent sleep monitoring and coronary CTA. Metrics reflecting coronary plaque characteristics were compared between patients with no or mild OSA with apnea hypoxic index (AHI) ≤15 and moderate-severe OSA (AHI>15). The associations of OSA with coronary plaque components were determined by logistic and linear regression analysis. Results: A total of 854 patients were enrolled in the study. Of these, 162 did not meet the inclusion criteria and of the remaining 692 patients 400 (57.8%) had moderate-severe OSA and 292 had no or mild OSA. Patients with moderate-severe OSA had a significantly higher total plaque volume, total non-calcified plaque (NCP) volume and total low density non-calcified plaque (LD-NCP) volume, and corresponding burden than those with no or mild OSA (all with p <0.05). Multivariate logistic regression analysis revealed that moderate-severe OSA patients are more likely to have any plaque, NCP and LD-NCP than those without no or mild OSA ( p <0.05). In addition, stepwise multivariate linear regression analysis further revealed an independent relationship between moderate OSA (1530) and, NCP volume, LD-NCP volume, NCP composition, and LD-NCP composition, following adjustment for traditional cardiovascular risk factors, compared to no or mild OSA (AHI<15) (all with a p <0.05). Moderate-severe OSA conferred a similar odds ratio for LD-NCPs (a high-risk plaque) as the usual cardiovascular risk factors. Conclusion: In this large cross-sectional study, OSA severity was associated with high-risk plaque features independent of traditional cardiovascular risk factors, suggesting an increased risk for cardiovascular events. Support: This study was supported by NSFC (Project 81870335), International Science & Technology Cooperation Program of China (No.2015DFA30160), Beijing Municipal Science & Technology Commission (No. Z141100006014057)